Absorption of Arabic Vocabulary into Indonesian (Analysis of Phonology, Morphology and Meaning in the Kbbi V Dictionary) - Hamid, Abdul; Garancang, Sabaruddin; Kasim, Amrah; Abu Nawas, Kamal (Journal of World Science, 2024)
This research aims to detail the process of absorbing Arabic vocabulary into Indonesian, emphasizing phonology, morphology, and semantics changes. This approach is library research using the listening, tapping, and free listening methods to collect data from various sources such as books, articles, networks, magazines, newspapers, and related documents. In phonological analysis, it was found that Arabic loan words used in daily communication experienced phonological changes, including sound changes, sound weakening, and changes in certain sounds. The results showed significant changes in the pronunciation of loan words. Meanwhile, semantic analysis reveals changes in meaning in borrowing Arabic words into Indonesian, including narrowing, widening, and changes in the meaning of adjectives, nouns, adverbs, and verbs, including changes in referential meaning. From a morphological perspective, changes in word classes are recorded, such as changes from nouns to adjectives, nouns to verbs, and other changes. The complexity of vocabulary absorption is illustrated through changes in these word classes. This research highlights that absorbing Arabic vocabulary into Indonesian is dynamic and complex. These findings have important implications for the evolution of Indonesian and interlanguage relations. Changes in phonology, semantics, and morphology reflect the complex interactions between these two languages, which will continue to develop along with changes and developments over time. This research provides deep insight into understanding the evolution of Indonesian and the dynamics of interlanguage relationships.